2020
DOI: 10.1038/s41598-020-59650-8
|View full text |Cite
|
Sign up to set email alerts
|

The integrated effect of salinity, organic amendments, phosphorus fertilizers, and deficit irrigation on soil properties, phosphorus fractionation and wheat productivity

Abstract: Soil degradation due to global warming, water scarcity and diminishing natural resources negatively impacts food security. Soil fertility deterioration, particularly phosphorus (P) deficiency, remains a challenge in the arid and semi-arid regions. In this study, field experiments were conducted in different geographical locations to investigate the effects of organic amendments coupled with P fertilization and irrigation on soil physical-chemical properties, and the growth, yield and quality of wheat. Applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 45 publications
3
51
0
1
Order By: Relevance
“…One of the main problems that affects soil productivity is a rising EC by increasing salts [9]. Applying organic amendments, including sewage sludge, has been widely reported to remediate saline soils and to alleviate salinity and sodicity stress in crops [36][37]. Our study showed that this did not happen in Villacañas, which coincides with similar studies in which EC did not only not increase, but even lowered [13], which was the case of treatments SS and CS.…”
Section: Discussionsupporting
confidence: 88%
“…One of the main problems that affects soil productivity is a rising EC by increasing salts [9]. Applying organic amendments, including sewage sludge, has been widely reported to remediate saline soils and to alleviate salinity and sodicity stress in crops [36][37]. Our study showed that this did not happen in Villacañas, which coincides with similar studies in which EC did not only not increase, but even lowered [13], which was the case of treatments SS and CS.…”
Section: Discussionsupporting
confidence: 88%
“…Salt adsorbing ability of organic amendments is also known to be considered in lowering the EC of soils [140]. The incorporation of different organic amendments in soils had often contributed to a slight increase in EC depending on the rate and duration of incorporation [139,146]. The increase in EC after the application of organic manures could be attributed to the presence of high amounts of K and Ca [141].…”
Section: Effects Of Organic Amendments On the Physical Chemical Andmentioning
confidence: 99%
“…The application of organic amendments in SAS is considered a useful and effective way to increase soil fertility and enhance crop growth [31,157]. The application of organic amendments in SAS increased the biomass yield of alfalfa, Medicago sativa [182]; barley, Hordeum vulgare [31]; cotton, Gossypium hirsutum [143]; maize, Zea mays [32,159,183]; onion, Allium cepa [142]; rice, Oryza sativa [31,153,184]; seepweed, Suaeda salsa [185]; sweet fennel, Foeniculum vulgare [186]; tomato, Solanum lycopersicum [187]; and wheat, Triticum aestivum [139]. The quantitative and qualitative improvements in the growth and yield attributes of crops as affected by abiotic stresses in the presence of different additives might be due to the enhanced photosynthesis, cholorophyll contents, stomatal conductance, water-use efficiency, and synthesis of metabolites [137,[188][189][190][191].…”
Section: Effects Of Organic Amendments On the Physical Chemical Andmentioning
confidence: 99%
“…Increasing soil salinity level (EC > 6 dSm − 1 ) promotes ion toxicity, nutritional imbalances, oxidative stress, decreasing the soil available water, cell division and changes in metabolic processes such as photosynthesis and disrupt plant membranes (Ding et al 2020, Hasanuzzaman et al 2014. In addition, the quality of sugar beet root juice has been also found to be adversely affected under high levels of salt in the soil (Dadkhah 2008, Wu et al 2003.…”
Section: Introductionmentioning
confidence: 99%